Development Strategies for Barter Markets to Support the Local Economy in Wulandoni Village, Wulandoni District, Lembata Regency - Maria Imakulata Pongge; Desiderius Yohanes Laba Puhun; Emiliana Martuti Lawalu (Universitas Tidar, 2026)
The barter market is an ancient trading system in which goods and services are exchanged directly without using money as a medium of exchange. In Wulandoni Village, Wulandoni District, Lembata Regency, the practice of barter markets is still preserved as part of local culture and also serves as a source of Village Original Revenue (PADes). This revenue is collected from traders' goods before market activities begin and is managed to fund basic needs, infrastructure development, local economic growth, and sustainable natural resource and environmental management. This study aims to identify and formulate development strategies for the barter market to support the local economy. The research employs a descriptive qualitative method using primary and secondary data collected through interviews, observation, and documentation. The results show that the barter market can enhance community purchasing power, strengthen social ties, and optimize local potential, particularly in marine products (fish, salt, lime) and agricultural produce (bananas, corn, cassava, vegetables, areca nuts, pineapples, and mangoes). However, challenges include limited types of goods, uncertainty in exchange value, and potential disagreements among traders. Recommended strategies include reinforcing existing local values, appointing market facilitators, fostering inter-regional collaboration, and organizing market zones. This research is expected to serve as a reference for local economic empowerment and provide a foundation for future studies by incorporating additional supporting variables